Plantar closing-wedge calcaneal osteotomy for the treatment of plantar ulcers in diabetic foot: a case report - Freitas, Cláudia Diniz; Rosa, Felipe Daniel Plata; Katayama, Martha Lúcia Silva; Silva, Daniel Araújo da Silva; Pires, Eduardo Araújo; Santos, Eduardo Cezar Silva dos (Journal of the Foot & Ankle, 2025)
Calcaneal ulcers in the diabetic foot present a complex challenge in limb preservation, as most of the outcomes are calcanectomy or limb amputation. These outcomes can significantly impact the patient, leading to functional limitations and difficulties with orthotic use. We report a case of the adaptation of a technique previously described by Gaenslen in 1931 for the treatment of calcaneal osteomyelitis. A 51-year-old diabetic patient with chronic injury in the calcaneal plantar region. Previous ulcers and debridements made primary closure challenging. A plantar subtraction osteotomy of the calcaneal bone was performed, facilitating primary chronic wound closure. The technique proved to be effective in treating calcaneal ulcer of a diabetic patient, preventing amputation, and promoting rehabilitation, in addition to enabling the early return of the patient to work activities. Level of Evidence IV, Therapeutic Study; Case Report.